Optimization of Xylanase Production through Response Surface Methodology by Fusarium sp. BVKT R2 Isolated from Forest Soil and Its Application in Saccharification - Ramanjaneyulu, Golla; Rajasekhar Reddy, Bontha (Frontiers in Microbiology, 2016)
Abstract Xylanses are hydrolytic enzymes with wide applications in several industries like biofuels, paper and pulp, deinking, food and feed. The present study was aimed at hitting at high yield xylanase producing fungi from natural resources. Two highest xylanase producing fungal isolates - Q12 and L1were picked from collection of 450 fungal cultures for the utilization of xylan. These fungal isolates - Q12 and L1 were identified basing on ITS gene sequencing analysis as Fusarium sp. BVKT R2 (KT119615) and Fusarium strain BRR R6 (KT119619), respectively with construction of phylogenetic trees. Fusarium sp. BVKT R2 was further optimized for maximum xylanase production and the interaction effects between variables on production of xylanase were studied through response surface methodology. The optimal conditions for maximal production of xylanase were sorbitol 1.5%, yeast extract 1.5%, pH of 5.0, Temperature of 32.5ºC, and agitation of 175 rpm. Under optimal conditions, the yields of xylanase production by Fusarium sp. BVKT R2 was as high as 4560 U/ml in SmF. Incubation of different lignocellulosic biomasses with crude enzyme of Fusarium sp. BVKT R2 at 37°C for 72 h could achieve about 45% saccharification. The results suggest that Fusarium sp. BVKT R2 has potential applications in saccharification process of biomass. Key words: Fusarium sp., Optimization, Response Surface Methodology, Saccharification, Submerged fermentation, Xylanase